E-MODUL BASED TOULMIN ARGUMENTATION MODEL TO ENHANCE PROBLEM-SOLVING SKILLS IN SCIENCE STUDENTS - Shofiyah, Noly; Eka Wulandari, Fitria; Intan Mauliana, Metatia; Yunita, Oktamira (Jurnal IPA Terpadu, 2024)
The rapid advancement of Society 5.0 demands students to possess strong problem-solving skills, encompassing systematic thinking, data analysis, and decision-making. However, preliminary studies reveal that students’ problem-solving abilities are generally low, necessitating innovative educational tools. This study aimed to develop and evaluate the effectiveness of an e-module based on Toulmin's Argumentation Model to enhance problem-solving skills among science students. Using a one-group pretest-posttest experimental design, the research involved 60 students from three science classes. The e-module was validated by experts in content, educational innovation, and technology, achieving an average validation score of 87.5%. The module was implemented across all classes, and significant improvements in problem-solving skills were observed, with an overall N-Gain score of 0.46, categorized as medium. These results indicate that the e-module is a valid, practical, and effective learning resource for improving problem-solving skills in science education.